The impact of father parenting style on youth purpose: Role of self-control and fear of missing out - Bianca Nur Dinar Ghaniyyah; Yulina Eva Riany; Diah Krisnatuti (Enlighten)
The role of parenting in shaping adolescents' psychological and behavioral development has long been recognized, but its impact in the context of the digital age remains underexplored. This study aims to analyze the influence of father parenting styles on adolescents' life goals (youth purpose), with self-control and fear of missing out (FOMO) as mediating variables. With a cross-sectional explanatory design, the research involved 1,144 adolescents aged 15 to 18 years in the Greater Jakarta area. Data were analyzed using Structural Equation Modeling (SEM). The findings demonstrate that authoritative fathering positively and significantly predicts youth purpose, both directly and indirectly, by enhancing self-control and reducing FOMO. In contrast, permissive parenting utilize a negative influence on self-control and, consequently, on youth purpose. Authoritarian parenting was found to increase FOMO, which in turn indicates a complex dual effect, both supporting and impairing the development of youth purpose depending on its interaction with self-control. These results underscore the critical role of father parenting style in shaping adolescents’ psychological regulation and goal-setting behavior. The study contributes to existing theoretical frameworks by linking parenting approaches to adolescent developmental outcomes in digital and culturally specific contexts. Practical implications include promoting authoritative parenting and designing interventions to strengthen adolescents’ self-regulation.